1998
DOI: 10.4141/a96-110
|View full text |Cite
|
Sign up to set email alerts
|

Effect of microbial enzyme supplementation on energy, amino acid digestibility and performance of pigs fed hulless barley based diets

Abstract: . Effect of microbial enzyme supplementation on energy, amino acid digestibility and performance of pigs fed hulless barley based diets. Can. J. Anim. Sci. 78: 625-631. Two experiments were conducted to investigate the influence of a microbial enzyme preparation on the digestibility and performance of starter-growing pigs fed hulless barley based diets. In the digestibility trial, eight pigs with an average initial body weight of 14 .3 ± 0.4 kg initial liveweight were surgically fitted with steered ileo-cecal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
3

Year Published

2001
2001
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 18 publications
2
11
3
Order By: Relevance
“…For instance, similar to the present study, carbohydrase supplementation did not improve ADG and nutrient digestibility in pigs fed rye-based or barley-based diets (Zijlstra et al, 2004;Thacker et al, 1992;Baas and Thacker, 1996). In contrast, other studies showed carbohydrase supplementation improved ADG in pigs fed barley, hull-less barley or wheat-based diets (Bedford et al, 1992;Van Lunen and Schulze, 1996;Baidoo et al, 1998). Zijlstra et al (2004) observed increased energy and DM digestibility, ADFI and ADG, but not feed efficiency with carbohydrase supplementation.…”
Section: Discussioncontrasting
confidence: 63%
“…For instance, similar to the present study, carbohydrase supplementation did not improve ADG and nutrient digestibility in pigs fed rye-based or barley-based diets (Zijlstra et al, 2004;Thacker et al, 1992;Baas and Thacker, 1996). In contrast, other studies showed carbohydrase supplementation improved ADG in pigs fed barley, hull-less barley or wheat-based diets (Bedford et al, 1992;Van Lunen and Schulze, 1996;Baidoo et al, 1998). Zijlstra et al (2004) observed increased energy and DM digestibility, ADFI and ADG, but not feed efficiency with carbohydrase supplementation.…”
Section: Discussioncontrasting
confidence: 63%
“…In view of the results reported in the literature (Taverner and Campbell, 1988;Van Lunen and Schulze, 1996;Baidoo et al, 1998;Yin et al, 2000a,b), it was expected that inclusion of enzymes would increase the DE and available AA for the MWB-based diet or MRB-based diet. Since the mechanism of such improvement seems to involve breakdown of the cell wall non-starch polysaccharides (NSP) this would have possible benefi ts in terms of reducing viscosity, as seen in poultry (Bedford and Classen, 1992;Campbell and Bedford, 1992) and to a lesser extent in pigs (Inborr et al, 1993).…”
Section: Discussionmentioning
confidence: 92%
“…Xylanase enzyme, in combination with ß-glucanase has been reported to improve hulless barley apparent ileal digestibility of nutrients (Yin et al, 2000a;2001a,b) and growth performance of young pigs (Baidoo et al, 1998). However, the effects of feed enzyme on nutrient utilization and nitrogen fl ow through the terminal ileum and excretion in faeces in growing pigs fed rice or wheat bran based diet were seldom reported in the literature.…”
Section: Introductionmentioning
confidence: 86%
“…Previously, a carbohydrase cocktail (cellulase, β-glucanase, and xylanase) supplemented to hull-less barley diets increased total-tract and ileal N digestibility 9 and 7%, respectively, and ileal digestibility of limiting amino acids 13 to 16% for weaned pigs (Baidoo et al 1998), and increased total-tract N digestibility 9% in grower pigs (Baas and Thacker 1996). Apparently, β-glucans or xylans did limit N digestibility or contained N that was released by carbohydrase.…”
Section: Discussionmentioning
confidence: 99%